The role of disaccharide complexes in triggering programmed cell death in cancer cells MCF-7 and HeLa - Schwarzlin, Romina; Pušenjak, Nika; Salam, Sejjad (European Journal of Oncology and Environmental Health, 2015)
Previous in vitro studies have confirmed that exposure of human endothelial cells to high glucose concentration induces significant cell death via apoptosis. The present studies therefore explore the options for treating cancer with cellobiose complex and natural compounds containing disaccharides. Our results show that the cellobiose complex containing cellobiose with vitamin C, sulphur and selenium isolated from a mixture of two cold plant extracts Capsicum chinense and Allium sativum induces cell death in HeLa cancer cells by activating caspase-3 and loss of mitochondrial integrity, but not in MCF-7 cancer cells or the immortalized cell line HaCaT. When we treated HeLa cancer cells with the laboratory-produced cellobiose alone, we found that a 10,000 x higher concentration was needed (100 mg/mL - 1,000 mg/mL), suggesting the important synergistic role of the other mentioned molecules in the complex, which enable the molecule of cellobiose to be more effective at lower dosages. This study therefore for the first time suggests that the complex formed of cellobiose, selenium, sulphur and vitamin C has an apoptotic and necrotic effect, which could be due to the modulation of a mitochondria-mediated intrinsic apoptotic pathway.